Against All Odds: Communication Privacy Management of a lesbian Couple in a Conservative Society - Sukmayadi, Vidi (International Journal Pedagogy of Social Studies, 2020)
This study aims at exploring the process of female homosexuals (lesbian) in disclosing and negotiating their stigmatised identity. A lesbian couple participated in the study’s in-depth interviews focusing on their experience and self-disclosing strategies on being a part sexual minority and living in Indonesia as a socially conservative religious-based country. The data were analysed within the guidelines of the Communication Privacy Management theory and idiographic approach. The analysis focuses on the process of coordinating the disclosing and closing acts that the lesbian couple carry out continuously in their relationships with others within their social life. The study is expected to assist in understanding how LGBT individuals negotiate and integrate their sexual identity within a socially conservative society.